The complex advertisement calls of Allobates myersi (Pyburn, 1981) (Anura: Aromobatidae) from São Gabriel da Cachoeira, Brazil - Simões, Pedro Ivo; Lima, Albertina P. (Zootaxa, 2011)
Pyburn (1981) described Allobates myersi from Waracá, Comisaria de Vaupés, in Colombia, including the new species in the Allobates femoralis group (sensu Silverstone 1976). Advertisement calls of A. myersi were described as a series of whistle-like note pairs, with dominant frequency between 3100–3800 Hz, emitted at a rate of 224.6 notes per minute. However, only a short, 1.4 s long sonogram was presented in the original paper. From its description, A. myersi has been mentioned only in a few revisionary studies, but no further data on calls were provided (Grant et al. 2006, Lötters et al. 2007).